The Changes in Intraocular Pressure After Phacoemulsification among Patients with Cataract: Intraocular Pressure After Phacoemulsification with Cataract - Kandhro, Prince Aakash Gul; Khoso, Ayaz Ali; Chachar, Nisar Ahmed; Deepa, .; Pirzado, Imran Ali; Ali, Shuaib (Pakistan Journal of Health Sciences, 2025)
Phacoemulsification is currently one conventional surgical treatments for cataract. It can significantly deepen the central and peripheral anterior chamber depth (PACD), relieve pupillary block state, not only effectively reducing intraocular pressure, but also significantly lowering the incidence of complications. Objectives: To evaluate the changes in intraocular pressure in patients with cataract following phacoemulsification surgery. Methods: A Prospective observational study was conducted at the “Department of Ophthalmology, Jinnah Postgraduate Medical Centre, Karachi” in a time frame of six months. Pre-operative intraocular pressure was measured using a Goldman applanation tonometer, and Phacoemulsification and IOL implantation were performed. Postoperatively, IOP was measured at the 7th day, 30th and 60th post-operative day. To assess the change in intraocular pressure, repeated-measure ANOVA was used. Stratification was done. Post-stratification independent sample T-test/One-way ANOVA were applied as appropriate. The p-value ≤0.05 was considered statistically significant. Results: There were 58.2% male and 41.8% female patients. Mean age was 62.59 ± 9.66 years. Mean cataract duration was 15.34 ± 5.42 months. In our study, mean pre-operative intraocular pressure, post-operative intraocular pressure at 7th POD, 30th POD and 60th POD were 17.71 ± 2.12 mmHg, 14.70 ± 2.14 mmHg, 13.22 ± 2.17 mmHg, and 11.72 ± 2.22 mmHg, respectively. A significant mean difference for intraocular pressure (P=0.001) was observed. Conclusions: The intraocular pressure was significantly decreased as the time increased from preoperative status to postoperative status at 60th POD.